Ilmu Administrasi Dalam Perspektif Good Goverment Dan New Public Management - Riyadi, Slamet (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2015)
This paper reviews the new perspective of public management and good goverment in the perspective of the administration and explains the differences between the two. New Public Management (NPM) at risk of leaving the service function for the poor and marginal. Therefore the perspective of good goverment improve NPM development movement. NPM paradigm without accountabilty would risk leaving the public interest. Accountbility as a basic pilar paradigm and the paradigm of good government can improve the weaknesses found in the paradigm previously thought. To implement public accountabilty is the transparency information. Transformation information system is the basic capital that can be used for the perfomance evaluation efforts of the public sector and to evaluate the implementation of public sector accountability for decisions and actions, namely the extent to which outcome and can be caused in the management of public service.